Strategi Keamanan Republik Indonesia di Selat Malaka - Wicaksa, Arif (Interdependence Journal of International Studies, 2020)
The security of the Malacca Strait is an issue that has long been discussed by many countries in the world because of the importance of the Malacca Strait as an international trade channel. Unfortunately, the security of the Malacca Strait is not well maintained. Crimes such as piracy, human trafficking, environmental damage, and other crimes continue to occur. Indonesia as one of the littoral state has resposbility for maintaining the security of the Malacca Strait. Using the concept of the Multi-Sum Security Principle and qualitative analysis, this research aims to look at the strategies that have been taken by Indonesia for the security of the Malacca Strait and the problems that hinder the achievement of security. It was found that the Government of Indonesia still uses a traditional military-centric approach in its security strategy. Non-traditional security strategies such as the eradication of corruption, poverty, to environmental damage around the Malacca Strait have not yet been fully integrated and implemented in the Indonesian Government's strategy. This causes the security in the Malacca Strait to be suboptimal.